WORKER'S HEALTH: disease and prevention in the workplace in health - Valério, Daniela Cristina; Rodolpho, Daniela (Revista Interface Tecnológica, 2023)
The objective of this work is to demonstrate the importance of how the health professional must be careful when having contact with substances that are harmful to health and that can cause allergic reactions and also serious illnesses that lead to absence from work in which also in this environment there are also that the worker goes through situations where they develop high levels of stress, anxiety and even depression. It is necessary to focus on the reduction of these diseases, accidents and absences from work, due to stress, anxiety, depression of health professionals, and on bibliographical research techniques through scientific articles where the intention is to present the importance of protection and safety measures for these professionals, the importance of health care, citing the main diseases and ways to minimize the effects they cause on the health of the health worker in general. Keywords: Health. Diseases. Protection.
Keywords: Health; Diseases; Protection